An instrument-free, screen-printed paper microfluidic device that enables bio and chemical sensing1. Issue 19 (7th October 2015) - Mohammadi, Saeed; Maeki, Masatoshi; Mohamadi, Reza M.; Ishida, Akihiko; Tani, Hirofumi; Tokeshi, Manabu
<x xml:space="preserve">Abstract</x> This paper describes a simple and instrument-free screen-printing method to fabricate hydrophilic channels by patterning polydimethylsiloxane (PDMS) onto chromatography paper.